A LANDIS-II extension for incorporating land use and other disturbances. (January 2016) - Thompson, Jonathan R.; Simons-Legaard, Erin; Legaard, Kasey; Domingo, James B.
Abstract: Forest landscape models (FLMs) are widely used to examine the influence of disturbances on long-term and broad-scale forest ecosystem dynamics. However, FLMs are not well-suited to simulating some types of management or disturbance regimes, including land-use change. Consequently, there are situations in which a researcher may wish to estimate the timing and location of events externally, either from a different model, empirical observations, or some other source, and then incorporate them into an FLM. We present Land Use Plus (LU+), an extension for the LANDIS-II FLM that allows users to integrate externally-developed, spatially and temporally explicit representations of land use or other disturbance into simulations. LU+ allows users to model the proximate effects of these events on forest composition and biomass, as well as subsequent dynamics, including tree establishment and the potential for future management. LU+ will significantly increase the breadth of research questions for which LANDIS-II may be appropriately used. Highlights: Land Use Plus (LU+) allows LANDIS-II users to integrate externally developed maps of land use or other disturbances. LU+ allows users to simulate forest protection and conservation easements. LU+ allows users to simulate tree planting at predetermined times and locations